Advances in the knowledge of plants used for snakebite in Colombia - Serna-González, Marcela; Blandón, Gabriel; Serna-González, Alejandro; Cogollo, Álvaro; Sasa, Mahmood (Ethnobotany Research and Applications, 2025)
Background: According to the National Health Institute of Colombia, 6231 snakebite cases were reported in 2023, but these cases poorly represent people from remote communities who did not seek medical treatment at the hospital and instead are treated through traditional medicinal knowledge. This review compiles information on plants species used by local communities or evaluated in laboratory for snakebite treatment in Colombia. It also discusses the bioprospecting potential of these plants for the development of complementary or alternative therapeutic options. Methods: The PRISMA framework was adopted to conduct a systematic review on plant species used for snakebite treatment, covering publications from January 1896 to May 2024 using databases such as ScienceDirect and Scopus. Gathered data included local name, plant part used, method of preparation, reported activity, and mode of administration Results: A total of 385 plant species belonging to 85 taxonomic families were identified as being used in the treatment of snakebite in Colombia. Based on the number of species, the most relevant plant families are Piperaceae (28), Fabaceae (27), Araceae (25), and Asteraceae (25). Notably, 66% of the species identified in this review have not yet been undergone through pharmacological or toxicological evaluation highlighting their potential for further evaluation. Conclusions: Future bioprospecting efforts could be valuable for identifying plant species with potential applications in snakebite treatment. However, to advance this field, several key challenges must be addressed: 1) improving the accuracy of plant identification to the species level; 2) conducting rigorous pharmacological evaluations to assess their efficacy against snakebite envenomation; and 3) establishing priorities to guide future bioprospecting research. Keywords: Ethnobotany, medicinal plants, native species, Neotropics, snakebite